1995
DOI: 10.1126/science.7701328
|View full text |Cite
|
Sign up to set email alerts
|

Ras-Dependent Induction of Cellular Responses by Constitutively Active Phosphatidylinositol-3 Kinase

Abstract: Phosphatidylinositol (Pl)-3 kinase is one of many enzymes stimulated by growth factors. A constitutively activated mutant, p110, that functions independently of growth factor stimulation was constructed to determine the specific responses regulated by Pl-3 kinase. The p110 protein exhibited high specific activity as a Pl-3 kinase and as a protein kinase. Expression of p110 in NIH 3T3 cells induced transcription from the fos promoter. Co-expression of dominant negative Ras blocked this response. When expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
403
11
6

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 529 publications
(441 citation statements)
references
References 19 publications
21
403
11
6
Order By: Relevance
“…In our experiments, MT binding to Shc and PI3K also seems to be essential for complete MAPK activation (data not shown). This is consistent with cooperation between the Ras and the PI3K pathways for full MAPK activation (Rodriguez-Viciana et al, 1994;Hu et al, 1995;Marra et al, 1995). However, high AP-1 activity is observed in the 250phe mutant (that does not bind Shc) even though the Erk1 activity displayed by this cell line is low.…”
Section: Discussionsupporting
confidence: 75%
“…In our experiments, MT binding to Shc and PI3K also seems to be essential for complete MAPK activation (data not shown). This is consistent with cooperation between the Ras and the PI3K pathways for full MAPK activation (Rodriguez-Viciana et al, 1994;Hu et al, 1995;Marra et al, 1995). However, high AP-1 activity is observed in the 250phe mutant (that does not bind Shc) even though the Erk1 activity displayed by this cell line is low.…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that PI 3-kinase through its protein kinase activity, regulates Ras, Raf, or ERK kinase (MEK) (Hu et al, 1995;Pandey et al, 1999;Bondeva et al, 1998). PI 3-kinase can directly activate MEK through protein phosphorylation Bondeva et al, 1998), or PDK-1 can directly bind and activate MEK (Sato et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In fact both wortmannin or p85 dominant negative e ciently block Gas6 survival activities, together with its mitogenic e ects (Goruppi et al, 1997) and Ras was indeed shown to be exclusively required for Gas6-dependent mitogenesis (this manuscript). Accordingly Hu et al (1995) reported that, at least in some systems, Ras might behave as a downstream PI3K e ector. Interestingly an overall reduction of cell survival was observed when RasN17, but not the Ras blocking antibody, was microinjected.…”
Section: Discussionmentioning
confidence: 99%